Synthesis and physical-chemical properties of 2-(5-(1Н-tetrazol-1-ylmethyl)-4-R-4Н-1,2,4-triazol-3-yltio)-acetic (propanoic), 2-, 4-(5-(1Н-tetrazol-1- ylmethyl)-4-phenyl-4Н-1,2,4-triazol-3- yltiometil)-benzoic acids and their salts - Y. S. Hulina; A. G. Kaplaushenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Scientists around the world pay considerable interest to chemistry of 1,2,4-triazole and 1,2,3,4-tetrazole thanks to the number of valuable properties of this class of compounds. Literary sources indicate that the core of 1,2,4-triazol and 1,2,3,4-tetrazol are fragments of many known drugs and bioactive compounds. Therefore, synthesis, studying physical, chemical and biological properties of the salts and acids that contain 1,2,4-triazole and 1,2,3,4-tetrazole is relevant both from a theoretical and practical perspective.